Evaluation of dietary fish meal analog with or without supplementation of natural feed additives as the substitute of fish meal in juvenile Japanese eel, Anguilla japonica - Jinho Bae; Seunghyung Lee; Mohammad Moniruzzaman; Ali Hamidoghli; Wonsuk Choi; Seunghan Lee; Taesun Min; Shin-Kwon Kim; Sungchul C. Bai (Frontiers in Marine Science, 2022)
We investigated the nine experimental diets containing fish meal (FM) and/or fish meal analog (FMA) as the major source of animal protein to determine the optimum FMA level as the substitute of FM protein in the diet of juvenile Japanese eel. In addition, two natural feed additives such as Song-Gang stone (SG) and Yucca meal (YM) were supplemented in the diet to evaluate their efficacy as the immunostimulants. The diets are as follows: 100% FM + 0% FMA in diet (FMA0), 90% FM + 10% FMA in diet (FMA10), 80% FM + 20% FMA in diet (FMA20), 70% FM + 30% FMA in diet (FMA30), 60% FM + 40% FMA in diet (FMA40), FMA0 + 0.4% SG (FMA0SG), FMA0 + 0.1% YM (FMA0YM), FMA20 + 0.4% SG (FMA20SG), and FMA20 + 0.1% YM (FMA20YM). Nine groups of Japanese eel each with three replicates were distributed (initial weight of 9 ± 0.2 g) in rectangular tanks receiving flow through water. Each group of the treatment consisted with 15 fish and fed one of the diets for 8 weeks. At the end of the feeding trial, fish fed with the FMA0 and FMA10 diets showed no significant differences in weight gain (WG), specific growth rate (SGR), feed efficiency (FE), and protein efficiency ratio (PER). Meanwhile, fish fed with FMA20, FMA30, and FMA40 diets showed significantly lower WG, SGR, FE, and PER than the fish fed with the FMA0 (control) diet. In addition, there were no significant differences among fish fed with the SG- and YM-supplemented diet groups. However, lysozyme activities in fish fed with the FMA10, FMA20, FMA30, and FMA40 were significantly lower than the fish fed with the FMA0SG, FMA0YM, FMA20SG, and FMA20YM diets. After 7 days of injection with V. Anguillarum, cumulative survival rates of fish fed with the FMA0SG and FMA0YM diets were significantly higher than the FMA0 diet group. The results revealed that the FMA could replace up to 10% of FM as a protein source in the diet of Japanese eel and both of the natural feed additives (SG and YM) could improve replacing rates of FMA from 10% to 20% without compromising growth and health status of fish.